Precursor effect on the Fe-doped cryptomelane (Fe-OMS-2) prepared via one-step sol-gel route as heterogeneous Fenton catalyst for degradation of methylene blue. Issue 1 (May 2020) - Awaluddin, A; Amiruddin, E; Anggraini, R; Indriyani, N; Siregar, SS
Abstract: The pristine cryptomelane (OMS-2) and Fe-OMS-2 (1%, 5%, and 10%) have been successfully synthesized by a one-step sol-gel method and characterized by XRD, SEM, BET surface area and AAS. The incorporation of Fe (III) within the structure of OMS-2 leads to an increase in surface area, pore-volume, and catalytic activity for the degradation of methylene blue (MB) and a decrease in the content of K + and average of pore diameter. The catalytic test indicated that the catalytic activity of Fe-OMS-2 1% is considerably higher that of pure OMS-2. The highest degradation of MB is 93.5% achieved using Fe-OMS-2 1% after 120 minutes of degradation time, the initial concentration of MB of 20 ppm, the catalyst concentration of 0.125 mg and the H2 O2 volume of 15 mL. The enhanced catalytic activities of Fe-OMS-2 compared to pristine OMS-2 for catalytic degradation of MB are associated with an increase in surface area, pore-volume, and smaller particle size. The results from catalytic studies imply that the metal doping is an effective strategy to enhance the catalytic activities of OMS-2 for degradation of MB.